Assessing the maturity of integration of health and social care in Finland - findings from a pilot study - Pesonen, Tiina; Sulander, Juhani; Tiirinki, Hanna; Räsänen, Pekka; Sahlström, Merja; Keskimäki, Ilmo; Sinervo, Timo (EMERALD GROUP PUBLISHING LTD, 2025)
Purpose Integrated care is the leading approach to developing health and social care services in Finland. After the national health and social care reform, the importance of assessing integration has been emphasized. The aim of this study was to pilot the SCIROCCO tool, which assesses integration maturity, in Finland. The SCIROCCO tool was translated and adapted to the Finnish health and social care context. The feasibility and utility of this tool for assessing the maturity for integration across health and social care in Finland were evaluated using empirical pilot data collected among employees of selected well-being service counties. The study also provided baseline information on the maturity of integration after the national health and social care reform.
Design/methodology/approach Employees (n = 111) of different personnel groups in health and social care services in four well-being service counties assessed the maturity of integration using a web-based survey. A pilot study design was used.
Findings The SCIROCCO tool was found to be useful for assessing the maturity of integration in health and social care within the well-being service counties. However, the tool requires further development to be fully adapted to the Finnish health and social care system and to assess integration across sectors. The results emphasize the need to understand the perspectives of different personnel groups on integration and to consider them in the development work.Originality/valueThis was the first study conducted in Finland that provided valuable insights into the assessment of integration across the health and social care sectors. This study establishes the foundation for future research and development in the field of integration assessment.